APLIKASI SOSIAL MEDIA KULINER MENGGUNAKAN API GOOGLE MAPS BERBASIS WEBSITE - Marlince N.K. Nababan; Meidika Sagala; Lengsina Sihombing; Fredy Sanjaya Ginting; Jen Chandra (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2019)
Culinary arts is one of the attractions for foreign tourists who hold a tour with the aim of enjoying various types of delicious food [1]. But if we want to get information about food or culinary in an area it is not easy especially for migrants who visit a new area. They cannot determine the food to be eaten because of the lack of information about the culinary in the area. The lack of information for the community certainly has an impact on culinary shops. Generally, many culinary store managers have difficulty in introducing marketed culinary, which makes the profits of the entrepreneurs managing the existing culinary stores decrease. Based on these problems, research will be conducted on issues with the aim of building a culinary media social application by using the Google Maps API. The results of this study are in the form of a culinary media social application by applying the Google Maps API method in helping culinary searches.